ANALYSIS OF RATE OF SHORELINE CHANGES ALONG THE COASTLINE OF KUALA TERENGGANU - Rojahan, Amir Auzan; Ibrahim, Illyani; Mohd Noor, Norzailawati (Malaysian Journal of Tropical Geography (MJTG), 2022)
The coastal zone is home to a substantial portion of the population (approximately 70%) and the hub of economic activity, including urbanisation, agriculture, and fisheries. Coastal erosion has led to the destruction of property and loss of land due to the corrosion of the shoreline. This research aims to identify the coastal erosion using the shoreline changes rate in Kuala Terengganu, Malaysia. The objectives of this study are i) to identify the location with the highest and lowest rate of shoreline changes in Kuala Terengganu and ii) to analyse the rate of changes along Kuala Terengganu shorelines. This study calculated net changes of shoreline position using the Linear Regression Rate (LRR) statistical method. Six (6) images are chosen between 2000 and 2019. The main findings show that the severe coastal erosion areas are Pantai Tok Jembal and Pantai Cendering, with 5.88 metres/year and 6.11 metres/year of the rate of change, respectively. The coastal erosion in Kuala Terengganu is due to the close development that intrudes the natural habitat. The extinction of vegetation are due to human activity and harsh weather conditions at the coastline area during monsoon season in the winter months. It is essential to prevent coastal areas because coastal erosions will destroy the property nearby and displace land as the coastline recedes. The best mitigation action for coastal erosion is monitoring the coastline.